Social Media Use by Citizen Science Projects: Characterization and Recommendations - Oliveira, Sofia S.; Barros, Bárbara; Pereira, Joana L.; Santos, Paulo T.; Pereira, Ruth (Frontiers in Environmental Science, 2021)
Citizen science projects often use social media, which is not surprising since they constitute a great opportunity to recruit, retain, and train volunteers. This study intended to quantitatively characterize the current use of social media by biodiversity-related projects and to reason on the best management practices. For this purpose, a database of projects was compiled and analyzed. The results revealed that 42% of the projects were present at least in one social platform, with Facebook being the most popular. Facebook posts were mainly intended to raise awareness and disseminating knowledge, but recruitment- and retainment-dedicated posts were also regularly shared.